2016
DOI: 10.1037/pas0000238
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Wechsler Intelligence Scale for Children–Fifth Edition: Exploratory factor analyses with the 16 primary and secondary subtests.

Abstract: The factor structure of the 16 Primary and Secondary subtests of the Wechsler Intelligence Scale for Children-Fifth Edition (WISC-V; Wechsler, 2014a) standardization sample was examined with exploratory factor analytic methods (EFA) not included in the WISC-V Technical and Interpretive Manual (Wechsler, 2014b). Factor extraction criteria suggested 1 to 4 factors and results favored 4 first-order factors. When this structure was transformed with the Schmid and Leiman (1957) orthogonalization procedure, the hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
103
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 86 publications
(261 reference statements)
24
103
1
2
Order By: Relevance
“…Similarly, the high H values (>.80) also suggests a dominant general factor that portends to be stable across studies. Thus, consistent with other frequentist EFA and CFA studies (e.g., Bodin, Pardini, Burns, & Stevens, ; Canivez, ; Canivez & McGill, ; Canivez, Watkins, & Dombrowski, , ; DiStefano & Dombrowski, ; Dombrowski, , , ; Dombrowski, Watkins, & Brogan, ; Dombrowski, Canivez, & Watkins, ; Dombrowski, Canivez, Watkins, & Beaujean, ; Dombrowski, McGill, & Canivez, , ; Watkins & Beaujean, ) and consistent with Frazier and Youngstrom (), the DAS–II appears to be an instrument dominated by a general factor.…”
Section: Resultssupporting
confidence: 87%
“…Similarly, the high H values (>.80) also suggests a dominant general factor that portends to be stable across studies. Thus, consistent with other frequentist EFA and CFA studies (e.g., Bodin, Pardini, Burns, & Stevens, ; Canivez, ; Canivez & McGill, ; Canivez, Watkins, & Dombrowski, , ; DiStefano & Dombrowski, ; Dombrowski, , , ; Dombrowski, Watkins, & Brogan, ; Dombrowski, Canivez, & Watkins, ; Dombrowski, Canivez, Watkins, & Beaujean, ; Dombrowski, McGill, & Canivez, , ; Watkins & Beaujean, ) and consistent with Frazier and Youngstrom (), the DAS–II appears to be an instrument dominated by a general factor.…”
Section: Resultssupporting
confidence: 87%
“…() with the Irish sample was consistent with results from other WISC–IV studies using both EFA and CFA (Bodin, Pardini, Burns, & Stevens, ; Canivez, ; Keith, ; Nakano & Watkins, ; Styck & Watkins, ; Watkins, , ; Watkins, Wilson, Kotz, Carbone, & Babula, ), with other versions of Wechsler scales (Canivez & Watkins, ,b; Dombrowski, McGill, & Canivez, ; Gignac, , ; Golay & Lecerf, ; Golay, Reverte, Rossier, Favez, & Lecerf, ; Lecerf, Rossier, Favez, Reverte, & Coleaux, ; McGill & Canivez, ; Nelson, Canivez, & Watkins, ; Niileksela, Reynolds, & Kaufman, ; Watkins & Beaujean, ), and intelligence tests in general (Canivez, , ; Canivez, Konold, Collins, & Wilson, ; Canivez & McGill, ; DiStefano & Dombrowski, ; Dombrowski, , ,b; Dombrowski & Watkins, ; Dombrowski, Watkins, & Brogan, ; Nelson & Canivez, ; Nelson, Canivez, Lindstrom, & Hatt, ) in showing the largest portions of variance were captured by the g factor and small portions of variance were associated with group factors. Three recent studies of the WISC–V have also yielded identical results (Canivez, Watkins, & Dombrowski, , ; Dombrowski, Canivez, Watkins, & Beaujean, ) with general intelligence dominating explained common variance and little unique explained common variance among the group factors. These results suggest that primary interpretation of these Wechsler scales (and other intelligence tests) should focus on the global score because it accounts for the largest portion of common variance.…”
Section: Introductionmentioning
confidence: 59%
“…Numerous studies of Wechsler scales and other intelligence tests have consistently found that the greatest portions of total and common variance are apportioned to or associated with the g factor, which is estimated by the Full Scale score, and much smaller portions of total and common variance are apportioned to the first‐order or group dimensions, estimated by the respective factor index scores (or CHC‐based composites). This has been documented in both EFA and CFA studies of the WISC–IV (Bodin et al ., ; Canivez, ; Keith, ; Nakano & Watkins, ; Styck & Watkins, ; Watkins, , ; Watkins et al ., ) and with other versions of Wechsler scales (Canivez & Watkins, ,b; Canivez et al ., , ; Dombrowski et al ., ; Golay & Lecerf, ; Golay et al ., ; Gignac, , ; Lecerf et al ., ; McGill & Canivez, ; Watkins & Beaujean, ; Watkins et al ., ). Further, these results are not unique to Wechsler scales as similar results were also observed with the DAS–II (Canivez & McGill, ), SB5 (Canivez, ), WASI and WRIT (Canivez et al ., ), RIAS (Dombrowski et al ., ; Nelson & Canivez, ; Nelson et al ., ), CAS (Canivez, ), WJ III (Dombrowski, , ,b; Dombrowski & Watkins, ; Strickland, Watkins, & Caterino, ), and the WJ IV Cognitive (Dombrowski et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The same substantive problems identified by Canivez and Watkins (); Canivez et al . (); Canivez, Watkins, and Dombrowski (); and Beaujean () with the CFA methods employed by the publisher with the US WISC‐V also apply to the WISC‐V UK . Among the noted problems was use of unweighted least squares estimation without explicit justification rather than maximum‐likelihood estimation as well as failure to fully disclose details of CFA (Kline, ).…”
Section: Introductionmentioning
confidence: 99%